2018
DOI: 10.1186/s13104-018-3256-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of communication technology and post-operative telephone surveillance during global urology mission

Abstract: ObjectiveCompliance with post-operative follow-up in the context of international surgical trips is often poor. The etiology of this problem is multifactorial and includes lack of local physician involvement, transportation costs, and work responsibilities. We aimed to better understand availability of communication technologies within Belize and use this information to improve follow-up after visiting surgical trips to a public hospital in Belize City. Accordingly, a 6-item questionnaire assessing access to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Telemedicine was used in surgery for clinical care, appointment reminders, patient education, and provider training. Clinical care included pre‐operative assessment ( n = 10, 5.6%) [24–33], post‐operative assessment ( n = 71, 39.9%) [34–105], and provider‐provider consultations ( n = 16, 9.0%) [106–121] (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Telemedicine was used in surgery for clinical care, appointment reminders, patient education, and provider training. Clinical care included pre‐operative assessment ( n = 10, 5.6%) [24–33], post‐operative assessment ( n = 71, 39.9%) [34–105], and provider‐provider consultations ( n = 16, 9.0%) [106–121] (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Mobile health is increasingly being embedded in healthcare delivery globally and across all specialties ranging from the use of Short Message Service (SMS) to complex applications on smartphones, and helping in bridging gaps in services in developing health systems [24]. Mobile health utilisation in surgical care including children's surgery [25] encompasses surveillance of surgical site infections [26][27][28][29], monitoring post-operative recovery [30,31], improving patient education and uptake of surgery [32], improving patients' return for follow-up care [33,34] and enhancement of follow-up after surgical missions [35,36]. In practice, POTFU augmented with photographs of the wound and video calls is expandable to post-operative monitoring of major surgeries and reduction of unnecessary hospital visits for wound reviews, similar to the report by Chua et al [37].…”
Section: Discussionmentioning
confidence: 99%
“…18 Similarly, a study by Rapp et al reported 51% of patients were compliant with a telephone follow-up 6 weeks after discharge from a urological procedure. 19 It is not possible to fully delineate the likely multifactorial causes underlying the higher contact feasibility found in Cameroon, which may include difference in telephone penetrance over time and in different locations. However, our findings suggest that earlier contact postdischarge may be more feasible than later contact which has the secondary benefit that earlier identification of off-trajectory patients is more likely to result in improved outcomes.…”
Section: Open Accessmentioning
confidence: 99%